PENGARUH VIRAL MARKETING TIKTOK TERHADAP KEPUTUSAN BERKUNJUNG KE M BLOC SPACE JAKARTA SEBAGAI WISATA BELANJA - Gusti Alia, Meliana; Sasrawan Mananda, IGPB.; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023), 2023)
The popularity of TikTok has soared since the COVID-19 pandemic. In Indonesia alone, users of the Tiktok platform have reached 22 million active users each month. One of the tourist attractions in DKI Jakarta that is currently visited by users of the social media platform Tiktok is M Bloc Space Jakarta. The method used is a mixed-method data analysis technique, which includes quantitative descriptive analysis and qualitative descriptive analysis. The sampling technique was purposive sampling, with a total of 100 respondents. Data collection techniques were carried out by means of observation, interviews, questionnaires, literature studies, and documentation. Data testing was carried out using the validity test, reliability test, linearity test, heteroscedasticity test, t test, and coefficient of determination test with SPSS version 25.0 for Windows. The results of the existing phenomena indicate that TikTok viral marketing has a positive effect on the decision to visit M Bloc Space Jakarta, with the results of the significance analysis test value of 0.000 0.05. The magnitude of the coefficient of determination is 75%. Other findings suggest that visitors who visit bring up new behaviours, namely an interest in shopping, so that M. Bloc Space Jakarta can be said to be one of the attractions for shopping tourism in the city of Jakarta.